Obstacles and Solution of Beyond Centers and Circle Time (BCCT) Implementation - Rafidiyah, Dina; Normulati, Sri (Universitas Negeri Semarang, 2020)
Early Childhood Education (PAUD) receives enormous attention from the government, because preparing the next generation needs to pay attention to how to foster children from an early age. One method of learning for young children that is fun and interesting is Beyond Centers and Circle Time (BCCT) or better known as the Center Method. The purpose of this study was to analyze the Obstacles and Solution of Beyond Centers and Circle Time (BCCT) Implementation in TK ABA 2 Banjarmasin.However, this method has not been widely applied in South Kalimantan Province, especially in Banjarmasin. TK Aisiyah Busthanul Athfal (ABA) 2 in Banjarmasin is the first kindergarten that has implemented in Banjarmasin. Therefore, this qualitative research was conducted with a case study approach, to explore the TK ABA 2 Kindergarten Banjarmasin process so that they could use BCCT, as well as the problems and solutions they had faced so that they could be input for other schools who wanted to also use this method. The principle and six teachers were interviewed to get information about the case. TK ABA 2 Banjarmasin started implementing BCCT in 2013. There are a number of things that need to be prepared, including preparing teachers especially in terms of educational background and center preparation including the availability of toys in each center. Obstacles can be resolved if all stake holders are dedicated to implement BCCT.